Comparison of the aquatic toxicity of diquat and its metabolites to zebrafish Danio rerio - Lanxin Shi; Xinru Wang; Yaoyao Dai; Wendong Zhou; Shenggan Wu; Bo Shao; Gorettie Nsubuga Nabanoga; Chenyang Ji; Meirong Zhao (Scientific Reports)
Abstract Diquat (DQ) is a non-selective, fast-acting herbicide that is extensively used in aquatic systems. DQ has been registered as the substitute for paraquat due to its lower toxicity. However, the widespread presence of DQ in aquatic systems can pose an ecological burden on aquatic organisms. In addition, DQ can degrade into its metabolites, diquat-monopyridone (DQ-M) and diquat-dipyridone (DQ-D) in the environment, while the ecological risks of the metabolites remain uncertain. Herein, the aquatic ecological risks of DQ and its metabolites were compared using zebrafish as model non-target organisms. Results indicated that DQ and its metabolites did not induce significant acute toxicity to zebrafish embryos at environmentally relevant levels. However, exposure to DQ and DQ-D resulted in oxidative stress in zebrafish larvae. DQ treatment led to increased levels of reactive oxygen species (ROS), malondialdehyde (MDA), and glutathione (GSH) in the larvae, while DQ-D increased internal MDA and GSH levels. Moreover, the activities of the antioxidative enzymes, superoxide dismutase (SOD) and catalase (CAT) were significantly suppressed by DQ and DQ-D. Besides, the expression levels of oxidative stress-related genes (Mn-SOD, CAT, and GPX) were disturbed accordingly after DQ and DQ-D treatments. These findings highlighted the importance of a more comprehensive understanding of the ecological risks of agrochemical substitutions as well as agrochemical metabolites. Such knowledge is crucial for significant improvements in agrochemical regulation and policy-making in the future.